Iodine enrichment of rainbow trout flesh by dietary supplementation with the red seaweed Gracilaria vermiculophylla - Valente, Luísa M. P. (2016)
The effects of different dietary inclusion levels (0, 5 and 10%) of IMTA-cultivated Gracilaria vermiculophylla on rainbow trout growth performance and flesh quality traits were evaluated. Flesh chemical composition (moisture, protein, lipid, vitamin E and iodine contents), sensory attributes and instrumental color were determined after a feeding period of 91 days with the experimental diets. The antioxidant activity of muscle carotenoids and hydrolysates was also determined by the 2,2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) methods. By the end of the experiment, fish fed CTRL or G5 diet reached similar body weight (215-220 g), but fish fed G10 weighed significantly less (167 g). Seaweed inclusion increased flesh moisture and decreased lipid content, with significant differences between the G5 and CTRL groups. Vitamin E content varied among treatments with CTRL fed fish presenting the highest levels of a-tocopherol. Iodine levels in the flesh increased with the seaweed inclusion, with fish fed G5 doubling its iodine content (214.5 mu g/kg) in relation to the CTRL (111.7 mu g/kg). Instrumental color showed that cooked fillets from fish fed seaweed-rich diets were more luminous (L*), less yellowish (b*) and more reddish (a*) than the CTRL. The sensory evaluation showed that fish fed with seaweed had juicier fillets than the CTRL with G5 presenting the most intense (pinkish) color. The instrumental differences are balanced in such away that the sensory panel perceived G5 as the sample with higher color intensity. Muscle carotenoid extracts presented no significant antioxidant activity through the ABTS and DPPH assays, whereas muscle hydrolysates showed similar antioxidant activity in all dietary treatments (ca. 33% through DPPH assay). The inclusion of Gracilaria sp. meal in diets for rainbow trout seems to be possible for up to 5%, as higher inclusion levels resulted in significantly smaller fish. The sensory panel perceived G5 as the sample with higher color intensity and juicier than the CTRL. Moreover, flesh iodine content doubled in fish fed G5, confirming seaweed as a natural and effective tool to increase the nutritional value of rainbow trout. Statement of relevance/impact of your paper to the general field of commercial aquaculture. This paper is relevant for the aquafeed industry and fish consumers. Fish meal has traditionally been the major dietary protein source for fish, but its reduction in aquafeeds is now a priority goal for the further expansion and sustainability of farmed fish production. Seaweeds may act as nutrient supply in fish, which in turn could ultimately function as vehicle of valuable compounds in human nutrition. This paper shows that 5% Gracilaria sp. meal can be a natural and effective tool to increase the nutritional value of rainbow trout flesh without impacting growth.